If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2y + -3x + 4y = 0 Reorder the terms: x + -3x + -2y + 4y = 0 Combine like terms: x + -3x = -2x -2x + -2y + 4y = 0 Combine like terms: -2y + 4y = 2y -2x + 2y = 0 Solving -2x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -2x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -2x + 0 = 0 + -2y -2x = 0 + -2y Remove the zero: -2x = -2y Divide each side by '-2'. x = y Simplifying x = y
| 6+5y-3=9y+27-7y | | -6.58+12=-5.42 | | -2x-3(X+5)=14 | | 2[5(x+y)-2(3x-4y)]= | | 7x=90+x | | 2x+95=6x+65 | | x*x-x+6=0 | | 4(t-4)+6t=5(2t+2)-9 | | 2x+10=4+1 | | x^2-2500= | | 3r-15=2r+10 | | x=-7y^6+11 | | m=b-x | | (3x-91)(x+3)= | | x^2-2500=0 | | x=7y^6+11 | | 4x+9=5x-6 | | 5r^2-35r+30=0 | | 80+0.3x=60+0.8x | | 11x-5=6c-20 | | 3x-13=4(x-3)+8 | | -10x-5y=50 | | 3(y-6)=2-27 | | g=4+2x^2 | | (5)+(7)= | | g=4-2x^2 | | 4y*(11y-14)=6-3y | | (2x-1)(x-13)= | | 4(y-2)=10-2y | | 0=6a+48 | | 11n^2-7n-2=-6+8n^2 | | 3(x+9)=2x-6 |